The effect of the enhanced recovery after surgery program on radical cystectomy: a meta-analysis and systematic review - Zhou, Yongheng; Li, Rongyang; Liu, Zhifeng; Qi, Wenqiang; Lv, Guangda; Zhong, Minglei; Liu, Xigao; Zhu, Meikai; Jiang, Zhiwen; Chen, Shouzhen; Shi, Benkang; Zhu, Yaofeng (Frontiers in Surgery, 2023)
Background Bladder cancer is the ninth most common malignant tumor worldwide. As an effective evidence-based multidisciplinary protocol, the enhanced recovery after surgery (ERAS) program is practiced in many surgical disciplines. However, the function of ERAS after radical cystectomy remains controversial. This systematic review and meta-analysis aims to research the impact of ERAS on radical cystectomy. Methods A systematic literature search on PubMed, EMBASE, SCOPUS, and the Cochrane Library databases was conducted in April 2022 to identify the studies that performed the ERAS program in radical cystectomy. Studies were selected, data extraction was performed independently by two reviewers, and quality was assessed using a random effects model to calculate the overall effect size. The odds ratio and standardized mean difference (SMD) with a 95% confidence interval (CI) served as the summary statistics for the meta-analysis. A sensitivity analysis was subsequently performed. Results A total of 25 studies with 4,083 patients were enrolled. The meta-analysis showed that the complications (OR = 0.76; 95% CI: 0.63–0.90), transfusion rate (OR = 0.59; 95% CI: 0.39–0.90), readmission rate (OR = 0.79; 95% CI: 0.64–0.96), length of stay (SMD = −0.79; 95% CI: −1.41 to −0.17), and time to first flatus (SMD = −1.16; 95% CI: −1.58 to −0.74) were significantly reduced in the ERAS group. However, no significance was found in 90-day mortality and urine leakage. Conclusion The ERAS program for radical cystectomy can effectively decrease the risk of overall complications, postoperative ileus, readmission rate, transfusion rate, length of stay, and time to first flatus in patients who underwent radical cystectomy with relative safety. Systematic Review Registration https://inplasy.com/, identifier INPLASY202250075.